Kinetic and thermodynamic studies of malachite green adsorption using activated carbon prepared from desert date seed shell - Yunusa, Umar; Usman , ,Bishir; . Ibrahim, . Ibrahim, Muhammad Bashir Muhammad Bashir (جامعة الوادي - university of el oued, 2020)
The negative effect of high concentration of dyes in the aquatic environment on humans and aquatic plants prompted this research. The adsorption of hazardous malachite green (MG) from aqueous solution using activated carbon derived from desert date seed shell (DDAC) was examined. Batch equilibrium technique was employed to study the effect of contact time (5-120 min), initial concentration (20-100 mg dm-3) and temperature (303.15-333.15 K) on the adsorption capacity of the prepared adsorbent. Experimental data were analyzed using five kinetic models: pseudo-first-order, pseudo-second-order, Elovich, intraparticle diffusion and Boyd models and it was found that the pseudo-second-order model fitted the adsorption data most with the highest correlation (R2 = 0.9999). The overall adsorption process appears to be jointly controlled by intraparticle diffusion and film diffusion mechanisms. Studies of thermodynamic behavior revealed negative values for ΔG (-11.45 to -13.42 kJ mol-1), and a positive value for ΔH (8.39 kJ mol-1) and ΔS (0.065 kJ mol-1 K-1). These indicated the feasibility, endothermicity and spontaneity of the removal process. The results demonstrated that the adsorbent could be exploited in the removal of MG from aqueous solution.
Article
Keywords: Adsorption; Activated Carbon; Malachite Green; Kinetic; Thermodynamic.